Delignifikasi Limbah Kulit Nanas untuk Produksi Biogas Melalui Metode Delignifikasi MAE (Microwave Asissted Extraction) dengan Pelarut - Safaah Nurfaizin; Sufrotun Khasanah (Fakultas Teknik dan Rekayasa, 2024)
Biomass as an energy source is very compatible with Indonesia's natural resources. Pineapple peel waste contains a lot of cellulose, which can be used as a renewable energy source. However, the presence of lignin in pineapple skin stops the hydrolysis process. So, this research looks at how the MAE (microwave assisted extraction) delignification method optimizes pineapple peel waste cellulose. The results of research by changing the operating temperature to 70oC, 80oC, and 90oC show that lignin solubility increases with operating temperature. To compare, the control sample had lignin and cellulose solubility of 2.68% and 17.39% of the sample weight, while the sample delignified with MAE had a solubility of 9.04% and 29.42% of the sample weight at an operating temperature of 90oC, for two twenty minutes, and with a ratio of 1:20 (w/v). After delignification, analysis continues using FTIR to compare the organic components in the sample. In the graph of microwave pretreatment spectra results, wide absorption is found at 3320 and 3333 cm-1; The spectra results without pretreatment show free O-H vibrations from a group of hydroxyls in the cellulose molecule. The peaks that have changed can be seen in the graph of the microwave pretreatment spectrum results, which shows wave values ​​of 1625 and 1630 cm-1, and shows the vibration of the aromatic chains in lignin. The cellulose peaks are 1032 and 1034 cm-1. These peaks are glucose ring stretching, changes in the C-H form in hemicellulose and cellulose.